Peripheral T-cell lymphoma mimicking classic Hodgkin's lymphoma in a patient presenting with fevers of unknown origin. (2nd February 2018) - Butler, Caitlin; Skelton, William Paul; Patel, Arpan; Mahtta, Dhruv; Zhuang, Yi; Cherabuddi, Kartik; Shah, Kairav; Markham, Merry
Abstract : A 52-year-old man presented to our hospital for further workup of fever of unknown origin after an extensive workup at an outside hospital had failed to reveal a diagnosis. At the outside hospital, he underwent excisional biopsy of the left supraclavicular lymph node, which showed non-necrotising granulomatous changes, and a bone marrow biopsy which showed a normocellular marrow. He was discharged without a diagnosis with recommendations to present to a tertiary hospital. During his admission, his hospital course was complicated by new direct hyperbilirubinaemia and eosinophilia, prompting liver and skin biopsies which showed CD30+ and CD3+ cells. He subsequently underwent left axillary lymph node biopsy, which was reported as 'classic Hodgkin's lymphoma'. With worsening lab values and T cells noted on liver and skin biopsies, excisional lymph node biopsy was sent to the National Institute of Health, where it was confirmed patient had peripheral T cell lymphoma.